Trans-blepharoplasty lateral volumizing brow lift in the management of lateral upper eyelid dermatochalasis - Elhamaky, Tarek (Aesthetic Medicine, 2024)
Purpose: To investigate the efficacy of simultaneous upper eyelid blepharoplasty (UEB), internal browpexy (IB), and brow fat pad suspension suture (BFPSS) for periorbital rejuvenation. Methods: a prospective study of 96 eyelids of 48 patients who underwent simultaneous UEB, IB, and BFPSS was conducted. All patients underwent a periorbital evaluation and patient satisfaction was evaluated at baseline, 1 week, 3 months, and 6 months after the surgery. Results: The mean baseline BOE increased significantly from 37.5±2.9 points to 81.5±4.6 points at the 12-month follow-up. The mean baseline eyelid eyebrow distance (LBD) increased significantly from 19.1± 0.6 to 21.5± 1mm at the 12-month follow-up. The mean baseline pretarsal space increased significantly from 2.6± 0.58 to 4.5± 0.31mm at the 12-month follow-up. Baseline lateral dermatochalasis classification was graded into grades 1, 2, and 3 in 28 (29.16 %), 50 (52.09%), and 18 (18.75%) eyelids, respectively. At the 12-month follow-up, grade 0 was recorded in 87 (90.6 %) eyelids, and grade 1 was recorded in 9 (9.4 %) eyelids. Conclusions: Our cohort highlights how concurrent BFPSS and QIB are minimally invasive adjuncts to UEB in the treatment of lateral dermatochalasis of the upper eyelid.